Influence of viscosity on chondrogenic differentiation of mesenchymal stem cells during 3D culture in viscous gelatin solution-embedded hydrogels. (10th February 2021) - Lee, Kyubae; Chen, Yazhou; Li, Xiaomeng; Kawazoe, Naoki; Yang, Yingnan; Chen, Guoping
Abstract: Differentiation of human bone marrow-derived mesenchymal stem cells (hMSCs) is regulated by a variety of cues of their surrounding microenvironments. In particular, mechanical properties of cell culture matrices have been recently disclosed to play a pivotal role in stem cell differentiation. However, it remains elusive how viscosity affects the chondrogenic differentiation of hMSCs during three-dimensional (3D) culture. In this study, a 3D culture system that was established by embedding viscous gelatin solution in chemically cross-linked gelatin hydrogels was used for 3D culture of hMSCs in gelatin solutions with different viscosities. The influence of solution viscosity on chondrogenic differentiation of hMSCs was investigated. Viscous gelatin solutions promoted cell proliferation in the order of low, middle and high viscosity while elastic hydrogels restricted cell proliferation. High viscosity gelatin solution led to increased production of the cartilaginous matrix. Under the synergistic stimulation of chondrogenic induction factors, high viscosity was beneficial for the chondrogenic differentiation of hMSCs. The results suggested the role of viscosity should be considered as one of the dominant mechanical cues affecting stem cell differentiation.